A Langmuir‐Kinetic Model for CVD Growth from Chemical Precursors1. Issue 7 (7th August 2013) - Raj, Rishi; Krumdieck, Susan P.
Abstract : A time‐dependent decomposition parameter is added to the classic Langmuir adsorption model to derive an expression for the growth of CVD films where chemical precursors are converted into the solid state upon arrival on a hot substrate. Three regimes of behavior emerge from the model; at low temperatures decomposition occurs faster than desorption, at intermediate temperatures the decomposition is slower than desorption, and at high temperatures the growth becomes flux‐limited such that all arriving vapor molecules convert to the solid phase. The relative dominance of these regimes varies with the impingement rate. In an Arrhenius plot, the asymptotic predictions from the model are matched with published experimental measurements1 2 for the growth of titania films from an alkoxide precursor; this exercise yields 135 kJ mol −1 as the activation energy for the decomposition reaction, and ∼92 kJ mol −1 for desorption. A molecular vibration frequency for decomposition of adsorbed vapor molecules is calculated to be approximately 6 × 10 11 s −1 . The middle regime, which is more prominent at low impingement rates and intermediate temperatures, is expected to promote step coverage. Abstract : A time‐dependent decomposition parameter is added to the classical Langmuir adsorption model to develop a model for CVD growth kinetics. The results, presented in the form of a processing map, separate into three regimes: low temperature, intermediate temperature, and high temperature. The middle regime, which is prominent at low impingement rates and intermediate temperatures, is expected to promote step‐coverage.